Edith Wharton and the politics of race - Kassanoff, Jennie Ann (Cambridge Univesity Press, 2004)
Edith Wharton feared that the "ill-bred"(the foreign and poor) would overwhelm a native American elite. Drawing on a range of turn-of-the-century social documents, unpublished archival material and all of Wharton's novels, Jennifer Kassanoff argues that a more accurate picture of her appreciation of American culture and democracy develops through less engagement with these controversial views. She pursues her theme by documenting Wharton's spirited participation in turn-of-the-century discourses ranging from euthanasia and tourism to pragmatism and Native Americans